2021
DOI: 10.12973/eu-jer.10.1.455
|View full text |Cite
|
Sign up to set email alerts
|

Development of Indonesian Language Text Books with Multiculturalism and Character Education to Improve Traditional Poetry Writing Skills

Abstract: <p style="text-align:justify">This research aims to develop Indonesian Language textbooks with multiculturalism and character education for traditional poetry writing learning. This research uses a research and development approach until the discovery of a proper textbook. The subjects involved in this study were 101 elementary school fourth-graders, 33 teachers, and 2 Indonesian language and literature learning experts. Data analysis techniques at the need analysis stage through interactive models, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Besides, the intensity of outgroup contacts was also able to generate respect, appreciation and acceptance of religious minorities in schools (Saputri et al, 2019). The results of the study also confirmed the need for permeating multiculturalism and character education values in various learning materials, including the learning of language and literature, especially the learning of writing skills (Winarni et al, 2021), to tackle diversity issues in the learning processes (Doucette et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…Besides, the intensity of outgroup contacts was also able to generate respect, appreciation and acceptance of religious minorities in schools (Saputri et al, 2019). The results of the study also confirmed the need for permeating multiculturalism and character education values in various learning materials, including the learning of language and literature, especially the learning of writing skills (Winarni et al, 2021), to tackle diversity issues in the learning processes (Doucette et al, 2021).…”
Section: Discussionsupporting
confidence: 60%
“…In addition, character education is an effort to build children's character in the learning process (Muhtar & Dallyono, 2020;Putra & Hasanah, 2018). We have to instill character education and develop it from an early age because at this age children are in the process of growing and developing at this time, all children's characters develop and begin to form, not only character, even intelligence, children's psychological skills also grow and develop (Ferdiawan & Putra, 2013;Rokhman et al, 2014;Winarni et al, 2021). Character education is an effort to develop the value of goodness as the initial foundation of a just society (Nida, 2019;Silanoi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pada uji lapangan mendapat respon bahwa pelaksaan pembelajaran dengan bahan ajar yang digunakan menyenangkan dan mudah dipahami sesuai dengan kebutuhan pengguna. Winarni et al, (2021) melakukan penelitian hasil yang didapakan sama dengan hasil penelitian di atas bahwa bahan ajar yang dikembangkan yakni buku ajar keterampilan menulis kreatif terintegrasi dengan nilai multikulturalisme dan karakter pendidikan mendapatkan hasil bahwa keterampilan menulis puisi lebih meningkat, sehingga bahan ajar yang dikembangkan layak digunakan guru dan siswa. Penelitian yang dilakukan kepada mahasiswa Universitas Ahmad Dahlan dalam pengembangan bahan ajar mata kuliah analisis kompleks menunjukkan bahwa bahan ajar telah melalui tahap revisi dan dinyatakan valid, buku yang dikembangkan terdapat latihan sesuai dengan tahapan untuk menigkatkan berpikir kritis menggunanakan pertanyaan kenapa dan mengapa (Setyawan et al, 2020).…”
Section: Keefektifan Modul Ajar Mata Kuliah Perencanaan Pembelajaran ...unclassified